ANALISIS IMPLEMENTASI SISTEM MANAJEMEN PUSKESMAS (SIMPUS) DALAM MENUNJANG PELAYANAN REKAM MEDIS - Erwin Muhtaddin (Journal Of Applied Health Research And Development, 2022)
Background: Puskesmas is the primary pillar of health care in Indonesia and also organizes the first level of Community Health Efforts (UKM) and Individual Health Efforts (UKP). The Puskesmas prioritizes promotive and preventive efforts to achieve the best public health degrees in their working areas. In carrying out its functions, puskesmas have several authorities, one of which is carrying out medical record activities (PERMENKES, 2014). Methods: The research design used is descriptive research with a qualitative approach. The data collection method used is by using the in-depth interview method using an interview guide. The population in the study were all service officers who in carrying out their duties related to SIMPUS were 8 people, Inclusion Criteria: Service officers who used SIMPus, Officers who could apply Simpus, Willing to become informants, Exclusion Criteria: Officers who could not use SIMP, Polindes, Pustu , Dentistry that has not been connected to simpus Conclusion: Availability in the number and qualifications of human resource education involved in the use of E-Puskesmas/SIMPUS at the Curug Health Center is still a problem that needs to be considered to be pursued, so that it can support health services to the community, especially in the field of Medical Records and Health Information. Human resources are in accordance with educational qualifications, so the program can run well. Suggestion: Adding human resources, especially D3 Medical Records and Information graduates or other Health Degrees so that the Coordinator of the Medical Records Unit is not burdened with other responsibilities.